If Auschwitz is nothing against denialism - Di Cesare, Donatella (Polity Press, 2023)
"Ever since the end of World War II, when the sheer enormity of the Nazi crime against the Jews became apparent, there have been repeated attempts to deny that the Holocaust really happened. The existence of gas chambers was questioned and the testimony of survivors was thrown into doubt; the more witnesses spoke out, the more they were intimidated and attacked by a denialism that sought to present itself as a search for historical truth. The accusation of trickery and deception - so central to the centuries-old anti-Jewish hatred - continues to thrive in the present. Today, denialism takes a new and more insidious form: Jews are accused of exploiting the 'cult of the Holocaust' to justify the state of Israel and to take the reins of political power. Holocaust denial has merged with conspiracy theories, alleging the existence of a Jewish-controlled New World Order. Concisely and authoritatively, acclaimed philosopher Donatella Di Cesare reconstructs the evolution of denialism and sheds new light on one of the most troubling phenomena of our time." -- back cover.